Power Flow Analysis of the Electric Power System in Texturizing Section at Asia Pacific Fibers in Ghatal, West Bengal using ETAP Power Station 4.0 Software - Kumar Shaw, Vivek (Journal of Power Electronics and Devices, 2023)
Electric Power Flow Analysis (Load Flow) is a study of power flow to find the quantum of power in a network. Nowadays industries require captive power for their production departments to continue the process in the event of Utility failure and also for safety purposes. The power flow analysis gives the power available that will meet the requirements, or some extra power is required or in extreme cases load shedding. The analysis also gives the losses in the system, thus ascertaining the authorities to reduce the losses. This load flow analysis study takes the example of the implementation of the electric power system at PT. Asia Pacific Fibers in Ghatal of West Bengal, with centralized load characteristics (lumped load). Power flow analysis begins with calculating the active power and reactive power at each installed node (bus), the load on the transformer, the load on the line or conductor, the value of power losses, system voltage drops, and the power flow in the installed electric power system network. From the results of power flow calculations assisted by the ETAP (Electrical Transient Analyzer Program) program, it can be concluded that the electricity network system is good. The results obtained are that the difference between active power losses and reactive power losses on Load Bus 4 is too large. Meanwhile, the voltage drop still meets the standards according to the Text Report results on ETAP results confirming that the voltage drop is meeting the IEEE specifications.